Simplification of the Role of Public Relations - Angga Intueri Mahendra (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2020)
The image of a company can be seen from public relations performance. The more effective public relations division runs its functions in managing the company's image and dealing with problems, the more positive the reputation of the company internally and externally. However, in practice, the function of public relations in companies has started to shift and even obscure the initial concept. In 2012, a supplier company for construction materials in Batam City, Indonesia, experienced internal conflict. The employees conducted an organized protest in the yard of the company building. The protesters were not satisfied with the current wages and demanded a pay increment. This problem was successfully resolved by the mediation of public relations that found a middle ground between the company and workers. After this event, the company reformed the organizational structure by eliminating the public relations division. However, a question arises: what then is the role of public relations? This study aimed to seek the simplification of the role of public relations executed by company management. The study indicated that there was a simplification in the company towards the role of public relations. The simplification manifested by imposing the role and duties of public relations to the operational secretary, which has a different area of expertise, causing a division to handle multiple tasks. The management considered that the operational secretary can ask for help from the management team if it is not capable of carrying out public relations tasks. The other simplification was equating the role of public relations with marketing. Consequently, the public relations division was also burdened with selling the company's products.